Electrical Tandem Roller (ETR) Media for 4C Capabilities Based Stem Learning Elementary Schools - Cahyana, Cahyana; Hamdu, Ghullam; Lidinillah, Dindin Abdul Muiz; Apriliya, Seni (Universitas Pendidikan Ganesha, 2020)
Learning media is very useful to help students understand the concepts of learning material provided. The use of innovative learning media is still limited to the learning process, especially thematic learning. Thematic innovative learning media is more specifically developed with STEM-based learning based on 4C capabilities, namely the Media Electrical Tandem Roller (ETR). Media development is carried out using the Focus General Discussion (FGD) Method with a qualitative approach. The process of implementing this FGD stage involved the development team of STEM learning tools that aims to validate the media produced without going through field trials. ETR media based on the ability of 4C in elementary schools has been produced for STEM learning. This innovative learning media is expected to be used, especially for teachers in thematic learning in elementary schools.